Eksplorasi Etnomatematika pada Tugu Hari Jadi Kabupaten Dati II Tanah Laut - Dewi Indra Anggraeni; Bayu Agung Wicaksono; Liny Mardhiyatirrahmah (FKIP Universitas Mataram, 2025)
This study explores the ethnomathematics embedded in the architecture of the Tugu Hari Jadi Kabupaten Dati II Tanah Laut, addressing the persistent issue of low mathematical literacy among Indonesian students in PISA assessments. The research emphasizes the urgent need for culturally relevant pedagogy to make mathematics less abstract and more engaging, particularly given the lack of existing ethnomathematical studies focusing on specific monuments like this one. The primary objective was to identify the inherent mathematical elements within the monument's design and determine their educational applicability. Utilizing a qualitative ethnographic approach, the research successfully catalogued concepts from both plane geometry (rectangles, circles, octagons) and solid geometry (octagonal prisms, cylinders, and hemispheres), complete with their respective mathematical formulas for area, perimeter, and volume calculations, and the role of trigonometry. The findings offer a strong ethnomathematical interpretation, revealing the monument as a cultural artifact that harmoniously symbolizes local values such as balance, steadfastness, and divinity. Educationally, the monument serves as an authentic learning resource to visualize complex geometry, thereby providing valuable contextual material to increase student interest, motivation, and critical mathematical literacy skills in line with global standards.